Parenting styles, socioeconomic status and (non-)cognitive skills - Philipp Kugler; Martin Kroczek; Anne Zühlke (Institut für Angewandte Wirtschaftsforschung (IAW), 2022)
This paper analyzes the role of parenting styles, a recent topic in the economic literature. Using a novel latent class model, we investigate which parenting styles can be observed in the data and how parenting styles are related to parents' socioeconomic status and household composition. We identify four parenting styles. An authoritarian and an authoritative style closely resemble the styles proposed by psychologists. The two other styles are variations of these styles. The parenting styles are strongly associated with household income, education and whether a child is an only child. The results suggest that constraints in both time and (non-)cognitive skills of the parents restrict their choice. We find that children's skills, in particular non-cognitive skills, are strongly associated with the parenting style. Parenting styles that are associated with low household income and having more than one child are associated with lower skills of the child. Therefore, our results indicate that parenting styles might be an important factor in explaining the skill gap in early childhood between children from different socioeconomic origins.
Keywords: J13; J24; J62; 330; human capital; skills; parenting; child rearing; parenting style; social mobility; socio-economic status; topic modeling